Additional 4-week capecitabine during the resting periods after 6-week neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer: long-term oncologic outcomes - Park, Sang Woo (Ann Surg Treat Res, 2018)
PURPOSE: The aim of this study was to evaluate the long-term outcome of additional 4-week chemotherapy with capecitabine during the resting periods following a 6-week neoadjuvant chemoradiotherapy (NCRT) regimen, in patients with locally advanced rectal cancer. METHODS: Radiotherapy was delivered to the whole pelvis at a total dose of 50.4 Gy for 6 weeks. Oral capecitabine was administered at a dose of 825 mg/m(2) twice daily for 10 weeks. Surgery was performed 2–4 weeks following the completion of chemotherapy. RESULTS: Between January 2010 and September 2011, 41 patients completed the scheduled neoadjuvant therapy and surgery. The pathologic complete response rate, 5-year overall survival, and 5-year disease-free survival rates were 22%, 85.4%, and 78.0%, respectively. The 5-year systemic recurrence and 5-year local recurrence rates were 22% and 0%, respectively. CONCLUSION: Additional 4-week chemotherapy with capecitabine, during the resting periods following a 6-week NCRT regimen, has favorable long-term oncologic outcomes. Further randomized controlled trials are however necessary to evaluate if substantial improvement in local control is achieved with this additional chemotherapy modality for locally advanced rectal cancer.